Relationship Analysis of Consumption Patterns and Avoid Culture Food on Nutritional Status of Pregnant Mothers in Aceh Barat District - Saripah Nur; Nurjannah Nurjannah; Fahmi Ichwansyah (Universitas Syiah Kuala, 2019)
The nutritional status of pregnant women is something that must be considered because it can affect the health of the mother and baby and can even cause death for the mother and baby. However, there are several problems related to consumption patterns and the culture of abstinence from food in the community. Thus, the problem raised in this study is the unknown relationship between consumption patterns and food abstinence culture on the nutritional status of pregnant women in West Aceh Regency. The purpose of this study was to determine the relationship between food consumption patterns and food abstinence culture on the nutritional status of pregnant women in Aceh Barat Regency. This research is a combination of quantitative and qualitative research with a cross sectional study approach . The sample in this study were 342 pregnant women. The sampling technique was carried out using the Slovin formula. Data was collected using questionnaires and interviews, while the statistical test used was logistic regression using stata. The results showed that partially (partially) there was a relationship between food consumption patterns and the nutritional status of pregnant women in Aceh Barat District (p-value = 0.001), between food abstinence culture and nutritional status of pregnant women in West Aceh District (p-value = 0.005 ), between family income and the nutritional status of pregnant women in Aceh Barat Regency (p-value = 0.002) and there is a relationship between family income, food consumption patterns and the culture of food abstinence simultaneously on the nutritional status of pregnant women in Aceh Barat Regency (p-value below 0.05). It is recommended for the Puskesmas to continue to improve nutritional counseling services for pregnant women, so that the nutrition of pregnant women can be fulfilled and pregnant women must always pay attention to consumption patterns.